The MBA Is Dead: Long Live the MBA - Alvarado Cabrera, Gabriela; Iñiguez, Santiago (My University, 2021)
Over recent decades, the MBA has been one of the most in-demand post-graduate qualifications, despite periodic economic crises. Unlike other specialist programs, which have evolved more elastically or cyclically, demand for MBAs has remained steady, with the exception of some periods marked by special circumstances, like student VISA restrictions, or during the period marked by the COVID-19 pandemic, although the information at the time of writing points to a recovery.